Zespół słabości powikłany złamaniami kompresyjnymi kręgów i silnymi zespołami bólowymi kręgosłupa - analiza przypadków z propozycją postępowania terapeutycznego = Frailty syndrome with compression spine factures and severe back pain - the clinical analysis and suggested treatment - Emilia Główczewska-Siedlecka; Katarzyna Mądra-Gackowska; Alina Jaroch; Krystyna Nowacka; Zygmunt Siedlecki; Mateusz Szostak; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2016)
Główczewska-Siedlecka Emilia, Mądra-Gackowska Katarzyna, Jaroch Alina, Nowacka Krystyna, Siedlecki Zygmunt, Szostak Mateusz, Kędziora‑Kornatowska Kornelia. Zespół słabości powikłany złamaniami kompresyjnymi kręgów i silnymi zespołami bólowymi kręgosłupa - analiza przypadków z propozycją postępowania terapeutycznego = Frailty syndrome with compression spine factures and severe back pain - the clinical analysis and suggested treatment. Journal of Education, Health and Sport. 2016;6(12):536-542. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.213480 http://ojs.ukw.edu.pl/index.php/johs/article/view/4086         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 19.12.2016.         Zespół słabości powikłany złamaniami kompresyjnymi kręgów i silnymi zespołami bólowymi kręgosłupa - analiza przypadków z propozycją postępowania terapeutycznego   Frailty syndrome with compression spine factures and severe back pain - the clinical analysis and suggested treatment   Główczewska-Siedlecka Emilia1, Mądra-Gackowska Katarzyna1, Jaroch Alina1, Nowacka Krystyna2, Siedlecki Zygmunt3, Szostak Mateusz3, Kędziora‑Kornatowska Kornelia1   1. Katedra i Klinika Geriatrii, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 3. Klinika Neurochirurgii, Neurotraumatologii i Neurochiurgii Dziecięcej, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu             Streszczenie Niniejsza praca omawia przypadki 8 chorych hospitalizowanych w Klinice Geriatrii CM UMK z rozpoznanym wg kryteriów Fried zespołem słabości. U badanych chorych zaobserwowano spadek masy ciała w ciągu ostatniego roku, cechy depresji wg skali CES-D,  spowolnienie chodu oraz, osłabienie siły mięśniowej oraz bóle kręgosłupa o nasileniu 9 VAS. W badaniach obrazowych kręgosłupa rozpoznano złamania kompresyjne kręgów, które poddano zabiegowi wertebroplastyki uzyskując poprawę w zakresie bólu, następnie u chorych wdrożono rehabilitację ambulatoryjną oraz dietę wysokobiałkową, po około 3 miesiącach u każdego chorego uzyskano istotną poprawę stanu klinicznego. Chorzy przestali spełniać kryteria Fried, co dowodzi tego że kompleksowe i często wielodyscyplinarne postępowanie korzystnie wpływa na leczenie starszych chorych z zespołem słabości.   Słowa kluczowe: zespół słabości, złamanie kompresyjne kręgu, dieta, rehabilitacja, wertebroplastyka       Abstract Authors present the cases of 8 patients treated in the Department of Geriatrics of CM UMK with frailty syndrome diagnosed. Patients showed a weight loss during the last year, signs of depression in CES-D scale, gait downturn, muscle weakness and severe back pain - 9 VAS. By imaging study the spinal fractures were diagnosed and patients underwent vertebroplasty obtaining good recovery in pain. Then patients have been implemented rehabilitation and high-protein diet. After about 3 months for each patient a significant clinical improvement was achieved. Patients no longer meet the Fried's criteria for frailty. This proves that this complex and often multi-disciplinary proceeding is beneficial for the treatment of elderly patients with frailty syndrome.   Key words: frailty, spine copression fracture, diet, rehabilitaion, vertebroplasty